2012
DOI: 10.1155/2012/363964
|View full text |Cite
|
Sign up to set email alerts
|

Postpartum Depression: Screening, Diagnosis, and Management Programs 2000 through 2010

Abstract: The value and appropriateness of universal postpartum depression (PPD) screening remains controversial in the United States. To date, several PPD screening programs have been introduced and a few have been evaluated. Among those programs that have been evaluated, most report screening rates, diagnosis rates, or treatment initiation rates. Only four studies included patient outcomes such as the level of depressive symptoms at 6 to 12 months postpartum, and only two reported success in improving outcomes. Progra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
41
0
4

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(47 citation statements)
references
References 50 publications
2
41
0
4
Order By: Relevance
“…[2][3][4][5][6] Neither the United States Preventive Services Task Force nor the American College of Obstetrics and Gynecology has made recommendations regarding routine PPD screening. 7,8 The American Academy of Pediatrics, however, recommends universal screening in the early postpartum period and screening for parental depression at each well-child visit.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[2][3][4][5][6] Neither the United States Preventive Services Task Force nor the American College of Obstetrics and Gynecology has made recommendations regarding routine PPD screening. 7,8 The American Academy of Pediatrics, however, recommends universal screening in the early postpartum period and screening for parental depression at each well-child visit.…”
Section: Introductionmentioning
confidence: 99%
“…Although such discussion may be of value, its impact on outcomes is unknown, and to date, studies of referral after an initial or repeated screenings have found limited uptake of mental health services by the women referred from pediatric or obstetrical practices. 5,[32][33][34][35] It is therefore necessary to do studies of screening and repeated screening that actually include outcomes to determine whether assessments of risks or benefits can support evidence-based recommendations for rescreening.The factors associated with new elevation of PHQ-9 scores after a baseline screening score of less than 10 are similar to those associated with elevated scores in the more immediate postpartum period: history of depression, limited education, not being married, and anxiety. 3,4,11,12,20 We were unable to assess obesity, history of interpersonal violence, or social support, which have also been associated with PPD in some populations.…”
mentioning
confidence: 99%
“…En conjunto con lo señalado, se ha referido que un ideal de maternidad exigente, compartido por las mujeres y su entorno, genera temor a no cumplir con las expectativas y reticencia a aceptar emociones negativas no validadas socialmente [24][25][26] . La importancia atribuida a la comunicación adecuada de la sospecha de DPP es respaldada por investigaciones recientes que sugieren la necesidad de entrenamiento del personal de salud para efectuar un proceso de detección integrado a la práctica clínica, que contemple la psicoeducación y acompañamiento a mujeres con sospecha de DPP 27,28 . La evidencia cualitativa en países desarrollados destaca la relevancia que el personal de salud establezca vínculos positivos para la apertura de problemas emocionales, puntualizando la ventaja que supone la continuidad en los cuidados de la salud materno-infantiles para construir este vínculo 24,25 .…”
Section: Discussionunclassified
“…In a recent review of postpartum depression screening and management programs across settings, both United States and international (from pediatrics, primary care-, and communitybased), only a fraction were shown to improve maternal outcomes (26). This review highlighted multiple systems-level barriers to getting women into treatment including requirements for psychiatric evaluations, often off-site, before treatment is provided (26).…”
mentioning
confidence: 99%
“…This review highlighted multiple systems-level barriers to getting women into treatment including requirements for psychiatric evaluations, often off-site, before treatment is provided (26). To date, much of this work to "bridge the gap" between efficacy and effectiveness has been carried out in obstetrics or community medical settings caring for adults.…”
mentioning
confidence: 99%